Horizontal axis wind turbines passive flow control methods: a review. Issue 1 (June 2021) - Manerikar, Sudhanshu S.; Damkale, Sourabh R.; Havaldar, Sanjay N.; Kulkarni, Shubhanga V; Keskar, Yash A.
Abstract: In improving wind turbine torque and power output, the aerodynamic characteristics of wind turbines blades play an important role. Unleashing easy but efficient flow enhancement techniques over aerofoil sections used in horizontal axis wind turbines (HAWT) has become essential in the increasing demand for this source of renewable energy. These techniques or methods are primarily categorized into two kinds: active and passive. Active methods of flow control need energy expensewhereas passive flow control methods are needless of auxiliarypower. This paper investigates various passive flow control strategies that have great potential to boost the aerodynamics of blades of HAWT. The mechanisms and working principles, along with the findings from various experimental studies and CFD results for passive flow control systems are included in this article. Also, some of these studies are supported by demonstrating the lift and coefficient of drag (CD ) variation with the angle of attack (AoA). The review suggests simple, cost-effective ways of improving lift and controlling the aerofoil stalling behaviors to obtain higher power efficiency for HAWT.